A Non-Planar Iodinated Pyrrole Study. (4th August 2016) - Valenzuela-Hermosillo, E.A.; Pacheco-Sánchez, J.H.
ABSTRACT: Non-planar iodinated pyrrole structures were found through DFT calculations of geometry optimization, when doping one pyrrole molecule with iodine atoms. This take us to a new mono-iodinated pyrrole structure in which one pyrrole molecule is attacked with one iodine atom in a pyramidal configuration. Then, the pyrrole molecule was attacked with two and until four optimized linear iodine atoms in a pyramidal structure configuration. The corresponding potential energy curves were also constructed in order to know what kind of adsorption (physisorption or chemisorption) is obtained, considering physisorption as lower than ten kcal/mol, and chemisorption greater than twenty kcal/mol according to the literature. Finally, it is known that halogenated pyrrole is a highly conductive material required in several fields.